Acupoint catgut embedding improves senescence in a rat model of ageing by regulating mitophagy via the PINK1 pathway. Issue 8 (1st March 2021) - Zhou, Meiling; Yuan, Yumei; Lin, Zishu; Zhang, Bin; Qin, Wenluo; Liu, Yongqiang; Yang, Cong; Wang, Qi; Zhang, Hong
Abstract: Ageing population is a tough task worldwide, and the aggravating trend of ageing population in China brings enormous pressure to healthcare system. Chinese acupuncture has shown definite anti‐ageing effect as arthralgia relief, movement improvement, energy increase and immunity enhancement; however, the mechanisms underlying are far away from illumination. Increasing literature has highlighted the role of alterations in mitochondrial function as a potential central regulator in ageing biology; mitophagy plays a critical role in mitochondrial quality control. In the present study, we demonstrated that acupoint catgut embedding treatment ameliorated ageing‐related alterations in appearance, muscle function and spatial memory in rats, reduced degenerated cells in hippocampus, and maintained relatively normal structures in the hippocampus tissue and neurons. These changes were proved to be associated with the regulation of mitochondrial function and autophagic activity. Furthermore, we investigated part of the molecular mechanisms and demonstrated that the PINK1 other than PINK1–Parkin signalling pathway involved in the effects of acupoint catgut embedding, and the imbalancement between mitochondrial fusion and fission and stimulation of mitochondrial biogenesis may aggravate or compensate for impaired mitochondria. The factors act downstream PINK, and the interaction between them for mitochondrial homeostasis in this process remains to be identified.